CFD Modelling of Flow Interaction in the Breathing Zone of a Virtual Thermal Manikin. (March 2017) - Ivanov, Martin; Mijorski, Sergey
Abstract: The presented work partly reveals the development stage of a Virtual Thermal Manikin (VTM), equipped with additional breathing functionality. The methods used are based on Computational Fluid Dynamics (CFD) flow simulations and analysis. Real thermal manikins, as well as the VTMs, represent modern, highly complex tools for assessment of the occupants' thermal comfort, as well as for analyses of indoor air quality in real or virtual enclosed environment. Also, real thermal manikins can be equipped with auxiliary devices that mimic human activities such as breathing, sweating, sneezing, coughing and others. Recent research indicates the development of an advanced compact pneumatic system, designed for implementation in the thermal manikin, capable of simulating the breathing related processes in humans. That is why the development of supplementary functionalities of the VTMs is considered as an important factor in the described research area. Thus, the presented case study reveals CFD based model of human body, with steady state breathing phases simulating the real human breathing processes. The results considering the flow interaction in the breathing zone showed good visual illustration and representation of the real physical processes.